Evolução de pequeno leque aluvial quaternário no Planalto das Araucárias - Oliveira, Leandro (2014)
Alluvial fans are good indicators of environmental change and tectonic movement. Thus, it is proposed to investigate which factors influenced the alluvial fan at the mouth of 1st order channel of Chopim River basin at Paraná State. For this, the objectives were 1) identify evidence of neotectonic; 2) characterization stratigraphic units, 3) identification depositional physical processes; 4) seeking records of vegetation change and 5) establish chronological correlation with global events. As a methodological procedure was carried out: 1) field work; 2) laboratory work and 3) office work. The field work consisted of: a) establishment of the stratigraphic section HS12, descriptions and sampling of materials; b) topography in drainage basin of 1st order channel on alluvial fan; c) electromagnetic and manual surveys on the deposit of alluvial fan and d) structural survey on the slope. The laboratory work for the stratigraphic section HS12 on the bedside of the alluvial fan included: a) particle size analysis of the matrix; b ) reason of stable isotopes of carbon 13/12 (δ¹³C) and c) radiocarbon dating (14C). In relation to work in the office was held activities such as: a) treatment of grain size data of matrix by Sysgran; b) organization and interpretation of field descriptions and laboratory; c) photointerpretation and d) GIS. Based on the results, it is concluded that the evolution of alluvial fan occurs from 2 main times. In the first time, it is inferred tectonic movement type half-graben previous to the alluvial fan and subsequently the deposition of colluvial facies. In the second time, the occurrence of environmental changes affecting the water regime, accompanied by the change of C3 to C4 vegetation, which in turn causes morphogenetic processes. Simultaneous vegetation change occurs to the alluvial facies.